Effects of Self-Selection Diets Differing in Cereal Source and Protein Level on Broiler Performance - Razuki , Waleed M.; Abed, Mezhir K.; Al-Naif, Hussam H.N. (International Journal of Poultry Science, 2018)
Objective: An experiment was conducted to investigate the effects on broiler performance caused by the free choice of three-phase-feeding diets with different cereal sources (maize or wheat) and dietary protein levels. Materials and Methods: Four-hundred and eighty 1-day old Ross-308 male broiler chicks were used in a 42-day trial. The experiment consisted of 8 treatments, which are as follows: MN: Birds were fed a single maize-soybean diet with a normal level of dietary protein, WN: Birds were fed a single wheat-soybean diet with a normal level of dietary protein, ML: Birds were fed a single maize-soybean diet with a low level of dietary protein, WL: Birds were fed a single wheat-soybean diet with a low level of dietary protein, MNWN: Birds were fed a mixture of two diets of MN and WN, MLWL: Birds were fed a mixture of two diets of ML and WL, MNWL: Birds were fed on a mixture of the two diets MN and WL and MLWN: Birds were fed on a mixture of the two diets ML and WN. Each dietary treatment consisted of 4 replicates (15 birds/pen). Results: Normal protein levels in the free-choice feeding significantly increased the Body Weight Gain (BWG) and feed consumption for birds fed maize or wheat as single or mixed diets. Choice diets of normal and low levels of dietary protein achieved a BWG that was not significantly different from birds fed normal dietary protein. The most detrimental effects were shown in birds that were fed a low dietary protein and a wheat-based diet. Birds that were given free-choice feeding of maize or wheat tended to consume a diet containing wheat, irrespective of protein level. The results of this experiment indicate that feeding a wheat diet is more suitable for the Ross 308 strain than feeding maize. Conclusion: The level of dietary protein plays an important role in performance but feeding behavior depends mainly on the different sources of grain.